(untitled) (International Educators Conference, 2025)
This article examines the application of the project-based approach as an effective method for fostering intercultural competence in foreign language education. It evaluates the advantages of this approach compared to traditional instructional methods and multimedia-based learning. The paper provides examples of successful integration of various strategies to enhance learning outcomes. It concludes by underscoring the importance of adopting a comprehensive approach that combines diverse methodologies to develop students’ skills in intercultural communication.